Customer satisfaction with order fulfillment in retail supply chains: implications of product type in electronic B2C transactions - Thirumalai, Sriram; Sinha, Kingshuk K. (Journal of Operations Management, 2005)
AbstractThis paper focuses on the proverbial “last mile” of the retail supply chain – i.e., delivering products to the end‐customer – and highlights the need for recognizing product type differences in configuring order fulfillment processes in electronic business‐to‐customer (B2C) transactions. The following two questions serve as the motivation for the study: Do customer expectations of order fulfillment processes vary across product types? Should the product type matter in configuring order fulfillment processes? From the studies in the marketing literature, we infer that customer satisfaction assessments are based on customer expectations of order fulfillment processes, and that these expectations systematically vary across the three product types: convenience goods (e.g., groceries, home and office supplies), shopping goods (e.g., ready‐to‐wear men, women, and kids’ apparel), and specialty goods (e.g., desktop and notebook computers, and wedding dresses). In particular, we posit that ceteris paribus, customer satisfaction with order fulfillment will decrease moving along a continuum of product types, from convenience goods to specialty goods. The empirical analysis for this study is based on data collected on dimensions of customer satisfaction with order fulfillment from a sample of 256 firms engaged in electronic B2C transactions. Firms included in our study sample are such that their products can be classified into only one of three product types: convenience, shopping, or specialty goods. In essence, each firm in the study sample is a proxy for one of three product types. The results of the empirical analysis indicate that, on average, customers tend to have higher satisfaction levels with the order fulfillment process of convenience and shopping goods than with the order fulfillment process of specialty goods. We discuss the managerial implications of our results, contributions of the paper to the literature, limitations, and directions for future research.